2011
DOI: 10.1111/j.1365-2966.2011.19416.x
|View full text |Cite
|
Sign up to set email alerts
|

Astroinformatics of galaxies and quasars: a new general method for photometric redshifts estimation

Abstract: With the availability of the huge amounts of data produced by current and future large multiband photometric surveys, photometric redshifts have become a crucial tool for extragalactic astronomy and cosmology. In this paper we present a novel method, called Weak Gated Experts (WGE), which allows us to derive photometric redshifts through a combination of data mining techniques. The WGE, like many other machine learning techniques, is based on the exploitation of a spectroscopic knowledge base composed by sourc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 42 publications
4
51
0
Order By: Relevance
“…In the upper half we provide standard statistical indicators (see text for an explanation) used to evaluate the performances of photo-z methods. We also include the same indicators for Laurino et al (2011). In the lower half of the table, we report the fraction (in percentage) of outliers computed using a fixed threshold of 0.15, the more meaningful 1, and 2σ clipping thresholds and the values of skewness and kurtosis of the σ (Δz norm ) distributions.…”
Section: Experiments and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the upper half we provide standard statistical indicators (see text for an explanation) used to evaluate the performances of photo-z methods. We also include the same indicators for Laurino et al (2011). In the lower half of the table, we report the fraction (in percentage) of outliers computed using a fixed threshold of 0.15, the more meaningful 1, and 2σ clipping thresholds and the values of skewness and kurtosis of the σ (Δz norm ) distributions.…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…The redshift range starting from z = 0 up to the redshift z 1 = 0.115 includes 50% of the objects in the test set; the second redshift bin, using the range from z 1 = 0.115 to z 2 = 0.177, corresponds to an additional 25% of the sample; the third bin, using the range z 2 = 0.177 to z 3 = 0.345, corresponds to an additional 15% and, finally, the fourth bin includes all remaining objects (redshift >z 3 = 0.345). The last row reports the statistics in the redshift range [0.05, 0.6] corresponding to the same range covered in Laurino et al (2011). 1.8…”
Section: Experiments and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying this method, Cowperthwaite et al (2013) recently identified thirteen gamma-ray emitting blazar candidates from a sample of 102 previously unidentified sources selected from Astronomer's Telegrams and the literature. Using the X-ray emission in place of the 22 μm detection, Paggi et al (2013) proposed a method to select γ-ray blazar candidates among Swift-XRT sources considering those that feature a WISE counterpart detected at least in the first 3 bands, and with IR colors compatible with the 90% two-dimensional densities of known γ-ray blazar evaluated using the Kernel Density Estimation (KDE) technique (Richards et al 2004;D'Abrusco, Longo & Walton 2009;Laurino et al 2011 and reference therein), so selecting 37 new γ-ray blazar candidates (Fig. 2, left panel).…”
Section: Selection Methodsmentioning
confidence: 99%
“…There are many applications of machine-learning techniques in astronomy (see Borne 2009;Ball & Brunner 2010). So far, spectroscopically derived properties have mainly A&A 576, A132 (2015) been used as ground truth to estimate redshifts on photometric data, for example in Laurino et al (2011), Gieseke et al (2011), Polsterer et al (2013). In contrast less attention has been paid to the application of machine learning to the spectral data itself (see Richards et al 2009;Meusinger et al 2012), which can be mainly attributed to the "curse of dimensionality" (see Bellman & Bellman 1961).…”
Section: Introductionmentioning
confidence: 99%